TECHNOLOGY OF FORMING PRACTICAL COMPETENCES OF FUTURE SOCIAL WORKERS (Web of Teachers: Inderscience Research, 2025)
This article covers the technologies of forming practical competencies of future social workers. The author discusses in detail the importance of a technological approach in social pedagogical activity, the need for algorithmic thinking and the types of technologies in social work. It is emphasized that in order for a social worker’s work to be effective, he must thoroughly master such stages as diagnostics, planning, problem solving, control and analysis. The article also scientifically and theoretically substantiates the concept of tolerance and its role in the development of society.